RELATIONSHIP ANALYSIS BETWEEN USING WALKING AIDS AND FEAR OF FALLING IN OLDER ADULTS - Anastasia Putu Martha Anggarani; Raditya Kurniawan Djoar (Berita Kedokteran Masyarakat (BKM), 2020)
Fear of falling will result in reduced balance control and a reduction in self-confidence to prevent falls, which will further increase the incidence of falls in the elderly. One of the efforts that can be done to reduce the fear of falling which is a trigger for falling events is to take preventive measures to analyze these risk factors, but currently the risk factors associated with fear of falling in the elderly in Indonesia have not been analyzed. The purpose of this study is to analyze the relationship between the use of walking aids and the fear of falling on the elderly. The research design was observational analytic with cross sectional approach involving 155 elderly living in Surabaya Werdha Nursing Home. The sampling technique uses proportional random sampling method. Existing data were analyzed using Contingency Coefficient Test with a significance level of 0.05. The results of statistical tests showed that there was a relationship between the risk of falling and fear of falling with a correlation value of 0.367 with a significant level of 0.000 (p <0.05), a positive direction indicated by the value of B = 1.365. The use of walking aids has a very meaningful relationship with the fear of falling in the elderly.